Kryteria Zniszczenia Ciągliwego Spowodowanego Szczelina Osiowo-Symetryczna Obciążoną Ciśnieniem Hydrostatycznym - Wnuk, M. (Engineering Transactions, 1967)
This is a discussion of the ductile collapse process in the light of considerations of energy balance at the collapse of a perfect elastic-plastic medium with an axially symmetric crack under hydraulic pressure. The model of the crack proposed concerns the case in which the body satisfies the additional assumption of the plastic zone constituting a narrow layer in the plane of the crack. The critical pressure causing the gap to propagate is calculated from the energy condition and confronted with the value obtained from the condition of maximum strain. The results of the present work are also confronted with the relevant values known from the theory of collapse of brittle bodies (Griffith, Sneddon, Sack). It is shown that the type of load has an essential influence on the limit load and the type of collapse. The equations obtained can be useful for studies of wear of surfaces weakened by small cracks (surface defects) and subject to the action of very high pressures.